2017
DOI: 10.1111/gfs.12277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping vetch (Vicia sativa L.), field pea (Pisum sativum L.) and triticale (X Triticosecale) on dry‐matter yield, nutritive and ensiling characteristics when harvested at two growth stages

Abstract: This study aimed to investigate the effects of growth stage and legume proportion on the nutritive and ensiling characteristics of triticale–pea–vetch intercrop mixtures. The three‐species mixtures were sown at three seeding ratios to produce different legume proportions (low, medium and high proportions) and harvested at two growth stages. The six resulting forages were subsequently ensiled in mini‐silos. Forage dry‐matter (DM) yield, nutritive characteristics of fresh and ensiled mixtures and fermentation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…Numerous studies have shown that intercropping has substantial advantages in crop yield and many other benefits than monoculture cropping; this has been reported worldwide, including those in northwest China (Mu et al, 2013; Chen et al, 2014a; Hu et al, 2016), India (Nelson et al, 2018), France (Maxin et al, 2017; Kaci et al, 2018), Germany (Gronle et al, 2014; Munz et al, 2014), and the North America (Franco et al, 2018; Simpson et al, 2018). However, the published studies have rarely determined the processes of C and N accumulation in vegetative tissues and the remobilization capacity of the photosynthate to the grain sinks under intercropping systems.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies have shown that intercropping has substantial advantages in crop yield and many other benefits than monoculture cropping; this has been reported worldwide, including those in northwest China (Mu et al, 2013; Chen et al, 2014a; Hu et al, 2016), India (Nelson et al, 2018), France (Maxin et al, 2017; Kaci et al, 2018), Germany (Gronle et al, 2014; Munz et al, 2014), and the North America (Franco et al, 2018; Simpson et al, 2018). However, the published studies have rarely determined the processes of C and N accumulation in vegetative tissues and the remobilization capacity of the photosynthate to the grain sinks under intercropping systems.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in CP yield due to legume contribution in the red pea:cereal intercrops is one of the main advantages for including red pea in an intercropping system. Similarly, Maxin, Andueza, Le Morvan, and Baumont () found that the increase in proportion of legumes enhanced the nutritive quality of the cereal:legume intercrops; however, they also suggested that the choice of harvest timing will depend on the intended use. Thus, when farmers are aiming for better nutritive value of forage, they must harvest at early‐growth stage but when their interest is for a greater quantity of forage, they have to harvest at the dough‐milky stage of the cereal.…”
Section: Discussionmentioning
confidence: 98%
“…Different seed rates do not affect crude protein content. Average crude protein content for field pea and triticale mixtures, at the dough-milky stage of development of the cereal, is 163 g kg -1 (Maxin et al, 2016). In another research average crude protein content of field pea:oat mixture (75:25%), at the dough-milky stage of development of oat is 12.96% (Uzun and Asik, 2012).…”
Section: Cultivarmentioning
confidence: 96%